2022
DOI: 10.3389/fpsyg.2022.892822
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Accent Modulates the Effects of Orthographic and Phonological Similarity on Auditory Processing by Learners of English

Abstract: The cognate effect refers to translation equivalents with similar form between languages—i.e., cognates, such as “band” (English) and “banda” (Spanish)—being processed faster than words with dissimilar forms—such as, “cloud” and “nube.” Substantive literature supports this claim, but is mostly based on orthographic similarity and tested in the visual modality. In a previous study, we found an inhibitory orthographic similarity effect in the auditory modality—i.e., greater orthographic similarity led to slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This may have created a propensity for the subjects in this study to erroneously adopt it for English, which is their subsequent language, and could thus manifest as more mistakes in the task. In a similar vein, Frances et al (2022) suggested that rules in the native language can negatively impact the process of mapping orthography to phonology in the subsequent language, especially if the native language is transparent while the subsequent language is opaque. Additionally, a quantitative study showed that at least 50% of the most common words in modern Malay are borrowed from Arabic ( Zaidan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may have created a propensity for the subjects in this study to erroneously adopt it for English, which is their subsequent language, and could thus manifest as more mistakes in the task. In a similar vein, Frances et al (2022) suggested that rules in the native language can negatively impact the process of mapping orthography to phonology in the subsequent language, especially if the native language is transparent while the subsequent language is opaque. Additionally, a quantitative study showed that at least 50% of the most common words in modern Malay are borrowed from Arabic ( Zaidan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is important to keep in mind that the degree to which L1 influences L2 depends on interactions with noise or other acoustic manipulations such as accent (see Frances et al, 2022), and other factors known to affect lexical processing such as frequency and phonological neighborhood density among other linguistic properties (Dijkstra, 2003).…”
Section: Study Limitationsmentioning
confidence: 99%
“…With respect to language coactivation, studies comparing modality have mostly looked at the effects of orthographic versus phonological word form overlap across languages (cognates). Across several studies (e.g., Cornut et al, 2022; Dijkstra et al, 1999; Frances et al, 2022), cognate facilitation effects appear larger when word forms across languages are comparable in orthography (as compared to phonology). This suggests that orthography might influence language coactivation more strongly than phonological information.…”
Section: Introductionmentioning
confidence: 95%